The Impact of the Digital Divide on MSMEs’ Productivity In Indonesia - Lukas, Erica Novianti; Hasudungan, Albert (Universitas Prasetiya Mulya, 2023)
Although the adoption of information and communication technology (ICT) has been rapid, gaps still exist regarding various areas of access to ICT among micro, small, and medium enterprises (MSMEs), which are the backbone of Indonesia’s economy. This study investigates how the digital divide factors increase productivity among MSMEs in Indonesia. Drawing on previous studies, the digital divide factors consist of material access, motivational access, skill access, and usage access. In this study, the logistic regression model is used with SUSENAS 2019 data from BPS. The study finds the significance of skill and usage access galvanize MSMEs’ enthusiasm to adopt the ICT platform in their business activities. Conversely, with weak significance of motivational and material access, this study recommends more extensive endeavors of the ICT infrastructure in boosting MSMEs’ productivity in the state of economic policy making in Indonesia.